The Frying Temperature Test of Snake Fruits in Vacuum Frying (Vacuum Pump Type) - Suryadi Suryadi; Ainun Rohanah; Lukman Adlin Harahap (Universitas Sumatera Utara, 2016)
Food processing by cooking needs a special technique to maintain the nutrition of the food. This research was aimed to measure the effective frying temperature in vacuum frying (vacuum pump type). This research was carried out at Agricultural Engineering Laboratory, Faculty of Agriculture USU in March – April 2014 using non factorial randomized block design with five levels, i.e. 75oC, 80oC, 85oC, 90oC, and 95oC. Parameters observed were water content, loss of oil, organoleptic value, and economic analysis. The results showed that frying temperature had highly significant effects on water content, loss of oil, and organoleptic value, but it showed that there was no highly significant effect on taste. Economic analysis showed that investment with this equipment was non - profitable. Keywords: Snake Fruit, Temperature, Chips, and Vacuum Frying.